Frequency of acute kidney injury in women with preeclampsia at Shaikh Zaid Women Hospital, SMBBMU Larkana - Parveen, Tooba; Waheeda, Waheeda; Asma, Asma; Mehmoodah, Mehmoodah; Benish, Benish; Khushboo, Khushboo (Journal of Neonatal Surgery, 2025)
Objective: To Determine The Frequency Of Acute Kidney Injury In Women With Preeclampsia Present At Shaikh Zaid Women Hospital Cmc, Smbbmu Larkana. Study Design: Descriptive Cross-Sectional Study. Setting ; This Study Was Conducted At The Department Of Obstetrics & Gynaecology, Smbbmu, Larkana, Pakistan. Duration: Six Months After The Approval Of Synopsis From June 29, 2022 To December 28, 2022. Materials And Methods: All Patients Who Fulfilled The Inclusion Criteria And Visited To Smbbmu, Larkana Were Included In The Study. Informed Consent Was Taken After Explaining The Procedure, Risks And Benefits Of The Study. In Our Study, Written Consent Was Taken From All The Pregnant Preeclamptic Women And Recruited To Admit In Ward And Further Evaluated For Acute Kidney Injury. All The Collected Data Were Entered Into The Proforma. Results: The Mean ± Sd Of Age Was 29.8±5.6 Years. The Mean ± Sd Of Parity Was 2.2±0.7 With C.I (2.08…….2.31). Acute Kidney Injury Was Found In 26 (18.6%) Women. Conclusion.: It is to be concluded that acute kidney injury is prevalent in preeclamptic women. More studies are necessary with a larger sample size and with more parameters in multiple study centers in Pakistan are needed to validate the findings of the present study